Interpersonal and Intrapersonal Intelligences: Are they related to EFL Teachers’ Self-efficacy Beliefs? - Saidi, Mavadat (AJELP: Asian Journal of English Language and Pedagogy, 2020)
The teachers’ multiple intelligences and self-efficacy beliefs seem to determine their level of effective teaching. The current study was conducted to investigate the possible relationship between Iranian English teachers’ interpersonal and intrapersonal intelligences and their self-efficacy beliefs. It further tried to explore if there was a significant difference among their self-efficacy beliefs in terms of their teaching experience. In order to collect the required data to unfold the relationship between the interpersonal and intrapersonal intelligences and self-efficacy beliefs, 140 high school English teachers were asked to complete two questionnaires including the relevant items excerpted from McKenzie’s “Multiple Intelligences Inventory” and Tschannen-Moran and Woolfolk Hoy’s “Teachers' Sense of Efficacy Scale" and a Pearson product-moment correlation test was conducted. The results of the analysis revealed that the personal intelligences were related to the teachers' self-efficacy. Results of the t-test revealed a significant difference in teachers' efficacy considering their teaching experience. The findings suggested incorporating interpersonal and intrapersonal intelligence types in teacher education programs in order to increase teachers’ self-efficacy in the teaching context.